The novel approach of catalytic interesterification, hydrolysis and transesterification of Pongamia pinnata oil - Inam, Summayia; Hanif, Muhammad Asif; Rashid, Umer; Nadeem, Farwa; Alharthi, Fahad A.; Kazerooni, Elham Ahmed (Multidisciplinary Digital Publishing Institute, 2022)
The properties of biodiesel are completely dependent on the fatty acid profile of feedstock oils. Several feedstocks are not in use for biodiesel production because of the presence of unsuitable fatty acids in their oils. The present study was conducted to overcome this problem by the utilization of interesterification and hydrolysis processes. The present study reports biodiesel with much better cold flow properties than previous studies. Fatty acids present in Pongamia pinnata oil were optimized via interesterification and hydrolysis treatment of feedstock prior to alkali-catalyzed transesterification. The physiochemical properties of fuel were evaluated by standard test methods and the results were compared with EN 14214 and ASTM D6751 standards. Biodiesel composition was analyzed by a gas chromatographic analysis. The density, saponification and iodine values of the biodiesel derived from treated and non-treated oil were found to be within the range recommended by the international fuel standards. The acid values of biodiesel produced from non-treated and treated fractions were high (0.7–0.8 mg of KOH/g of oil), as compared to the biodiesel produced from non-treated and treated pure oil. The cloud points and pour points of biodiesel produced from hydrolyzed and interesterified oil were in the range of (8.1 to −9.6 °C) and (2.03 to −12.5 °C), respectively, while those of non-treated oil were in the range of (13.37 to −1.53 °C). These results indicate that treatments of oil specifically improved the low-temperature properties of biodiesel.